Anticancer Potential of Ginger: Mechanistic and Pharmaceutical Aspects - Pal Kaur, Indu; Kaur Deol, Parneet; Kiran Kondepudi, Kanthi; Bishnoi, Mahendra (Current Pharmaceutical Design, 2016)
Background: Multifaceted pathologies like cancers involve multiple targets. Failure of current treatment options modulating specific tumor target, evokes need for alternate approach of either combining several smart drugs or design a dirty drug that may simultaneously influence multiple targets to trigger a cascade of protective events complementing one another. Methods: Present review tends to unravel the mechanism of anticancer action of ginger and also address issues, which may limit its realization as a biotherapeutic. Results: Ginger exhibits a pleiotropy of antioxidant, anti-inflammatory, antiemetic, anticancer, and antimutagenic effects. In vivo and in vitro studies have established that phenolic components of ginger, particularly 6-gingerol and 6-shogaol induce apoptosis and autophagy and inhibit metastasis. The poor biological profile of ginger extract or its actives is due to its restricted biopharmaceutical properties. The gap in manifesting the curative/therapeutic effects of these agents can be plugged by assigning them with a suitable pharmaceutical couture. Conclusion: Hence, amalgamating the rational formulation design with observational folklore data available on herbal drugs/agents, complemented with scientific and precise in vitro and in vivo findings can bring out a class of safe, cheap, and effective curatives which can address multitarget diseases like cancers.
Keywords: apoptosis